Genome-Wide Identification and Characterization of the PP2C Family from Zea mays and Its Role in Long-Distance Signaling - Wu, Huan; Zhu, Ling; Cai, Guiping; Lv, Chenxi; Yang, Huan; Ren, Xiaoli; Hu, Bo; Zhou, Xuemei; Jiang, Tingting; Xiang, Yong; Wei, Rujun; Li, Lujiang; et al. (Plants (Basel), 2023)
The protein phosphatase 2C (PP2C) constitutes a large gene family that plays crucial roles in regulating stress responses and plant development. A recent study has shown the involvement of an AtPP2C family member in long-distance nitrogen signaling in Arabidopsis. However, it remains unclear whether maize adopts a similar mechanism. In this study, we conducted a genome-wide survey and expression analysis of the PP2C family in maize. We identified 103 ZmPP2C genes distributed across 10 chromosomes, which were further classified into 11 subgroups based on an evolutionary tree. Notably, cis-acting element analysis revealed the presence of abundant hormone and stress-related, as well as nitrogen-related, cis-elements in the promoter regions of ZmPP2Cs. Expression analysis demonstrated the distinct expression patterns of nine genes under two nitrogen treatments. Notably, the expression of ZmPP2C54 and ZmPP2C85 in the roots was found to be regulated by long-distance signals from the shoots. These findings provide valuable insights into understanding the roles of ZmPP2Cs in long-distance nitrogen signaling in maize.